"My Body is not Mine": Woman’s Oppression Portrayed in Layla AlAmmar’s The Pact We Made - Insani Djohar, Hasnul; Ghea Regita Budiantari; Nihayatun Ni’mah; Muhamad Rizky Farezi (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study analyzes the oppression and differences between modern life and family life in traditional conservative Kuwaiti society experienced by Dahlia, the main female character in The Pact We Made. This study aims to examine how oppression Dahlia experienced as a Kuwaiti woman and what are the differences between her modern life and her family's conservative traditional life. The researchers used a qualitative descriptive method to conduct this research. Primary data used in this study is a novel entitled The Pact We Made by Layla Alammar, while secondary data is another source related to research objectives. The researcher applies the theory of standpoint feminism by Sandra Harding and Nancy Hartsock and the concept of oppression by Iris Marion Young to show what form of oppression through the lens of standpoint feminism are experienced by the main character in this book. The results of the research show that the oppression experienced by Dahlia is a type of powerlessness and cultural imperialism. This is shown by Dahlia who is not allowed to make her own choices and feels unable to go against the traditional rules of her parents and Kuwait society which is still strong with a patriarchal culture that underestimates women.